2020
DOI: 10.1109/access.2020.2981365
|View full text |Cite
|
Sign up to set email alerts
|

A New Ionospheric Model for Single Frequency GNSS User Applications Using Klobuchar Model Driven by Auto Regressive Moving Average (SAKARMA) Method Over Indian Region

Abstract: The single-frequency users of Global Navigation Satellite System (GNSS) require an effective mathematical model that mitigate the dominant errors due to ionospheric delays. Klobuchar model approximately reduces ionospheric effect up to 50% through its coefficients in the navigation message, which is not sufficient for the GNSS single frequency users at critical applications. Hence, a new model, for Single Frequency GNSS User Applications using Klobuchar model driven by Auto Regressive Moving Average Method (SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…By comparison, it can be found that due to different frequencies of L1 and L2, the influence of the higher-order term of the ionosphere on L1 and L2 band signals is different. According to Equation (8) and Equation (11), the influence of the second-order term on L2 is about 2.11 times that on L1, and the influence of the third-order term on L2 is about 2.71 times that on L1 [41] .…”
Section: Figure3 Influence Of L1 and L2 Observation Of Each Gps Satementioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, it can be found that due to different frequencies of L1 and L2, the influence of the higher-order term of the ionosphere on L1 and L2 band signals is different. According to Equation (8) and Equation (11), the influence of the second-order term on L2 is about 2.11 times that on L1, and the influence of the third-order term on L2 is about 2.71 times that on L1 [41] .…”
Section: Figure3 Influence Of L1 and L2 Observation Of Each Gps Satementioning
confidence: 99%
“…Ionospheric delay is one of the main error terms in satellite-borne GPS POD technology. The variation of electron density distribution with time and space results in the complexity of ionospheric delay [10][11][12] . How to deal with ionospheric delay is an important factor to improve POD precision.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the ambiguity of the RZ CL code, CL amb , cannot be solved by the bit-boundary given its extremely long code duration (1500 ms). The ionospheric delay of each channel is solved as TEC × 40.3 /c f 2 using the Klobuchar algorithm [21,22], which is a curve fitting technique that considers eight inputted Klobuchar coefficients obtained from the navigation messages. This delay was found to be proportional to the TEC and inversely proportional to a square of the carrier frequency f and speed of light c. In this model, the value of 40.3 was the so-call Klobuchar factor [20], which is computed to reduce the ionospheric root mean square range error by 57% [23].…”
Section: Limitation Of Different Code Periods From Two Bands and Corresponding Processmentioning
confidence: 99%
“…That is to say, the amb CM is solved as "1" for the assist Equation ( 5) by the tracked bit edge. Hence, a simplified relationship of the two code phases (τ L1 , τ L2 ) is shown as: Klobuchar algorithm [21,22], which is a curve fitting technique that considers eight inputted Klobuchar coefficients obtained from the navigation messages. This delay was found to be proportional to the TEC and inversely proportional to a square of the carrier frequency f and speed of light c .…”
Section: Limitation Of Different Code Periods From Two Bands and Corresponding Processmentioning
confidence: 99%
“…Regional ionospheric models include polynomial model (POLY), spherical cap harmonic function (SCH), auto-regressive moving average (ARMA), etc. [ 6 , 7 , 8 ]. However, different models have different performance and spatial resolutions, and their applications in different regions need to be verified by further work.…”
Section: Introductionmentioning
confidence: 99%